Karakterisasi stem cell pulpa gigi sulung dengan modifikasi enzim tripsin (The characterization of stem cells from human exfoliated deciduous teeth using trypsin enzym) - Tri Wijayanti Puspitasari; Tania Saskianti; Udijanto Tedjosasongko (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: Now a days, treatment in dentistry, using tissue regeneration that based on the stem cells from human exfoliated deciduous teeth (SHED), grows rapidly. For several reason, the isolated and cultured SHED is difficult to be applied in Indonesia, therefore the modification is needed. This difficulties were caused by the pulp anatomy, the heterogeneous populations in the pulp chamber and the limitations of tools and materials at the laboratory. Purpose: This research was aimed to examine that the modifications of isolation and culture technique of SHEDs for characterization by using the marker of CD105. Methods: The research was experimental laboratory with the cross sectional design. The samples were the human exfoliated deciduous teeth from the children patients of Pediatric Dentistry Department of Universitas Airlangga Dental Hospital which matched the criteria. Dental pulps were isolated and cultured by using the modifications of Trypsin enzymes. Results: The healthy SHEDs could be produced from the modifications of isolation and culture and positively shown the expression of marker CD105 which were indicated by the fluorencent microscope. Conclusion: SHED which isolated and cultured by using the modified techniques, positively characterized by using marker CD105.Latar Belakang: Pengobatan kedokteran gigi berkembang dengan pesat terutama di bidang regenerasi jaringan berbasis Stem Cells from Human Exfoliated Deciduous Teeth (SHED). Di Indonesia, isolasi dan kultur SHED sulit sehingga perlu dilakukan modifikasi. Kendala ini muncul karena jaringan pulpa yang kecil, heterogen dan keterbatasan alat dan bahan di laboratorium. Tujuan: Penelitian ini bertujuan untuk meneliti modifikasi pada cara isolasi dan kultur SHED untuk karakterisasi menggunakan maker CD105. Metode: Jenis penelitian ini adalah eksperimental laboratoris dengan rancangan cross sectional. Sampel penelitian adalah gigi sulung dari pasien anak di Klinik Kedokteran Gigi Anak, Rumah Sakit Gigi dan Mulut Universitas Airlangga yang telah memenuhi kriteria. Pulpa gigi diisolasi dan dikultur dengan modifikasi enzim Trypsin. Hasil: SHED yang sehat hasil dari modifikasi teknik isolasi dan kultur positif menunjukkan ekspresi marker CD105 dengan berfluoresensi berwarna hijau dilihat melalui mikroskop fluoresen. Simpulan: SHED yang dikultur dan diisolasi dengan teknik modifikasi positif dikarakterisasi dengan marker CD105.